Minimally Invasive Vitreoretinal Surgery (25G, 27G) with High-speed Vitrectomy Cutter – Case Series - Krzysztof Broniarek; Katarzyna Michalska-Małecka (Okulistyka)
Introduction: The development of vitreoretinal surgery is inseparably linked to the gradual miniaturization and decreasing invasiveness of the procedure. The smallest available systems are 23G, 25G, and 27G, which are referred to as minimally invasive vitreoretinal surgery techniques. This paper presents the preoperative and postoperative results of three patients undergoing posterior vitrectomy using the 25G or 27G systems with the HIPERVIT probe (Alcon, USA). The effects were retrospectively analyzed in terms of changes in best corrected visual acuity, intraocular pressure, occurrence of complications, and changes in optical coherence tomography images of macular edema. Examinations were performed before and one day, two weeks, three months, and six months after vitrectomy. The potential benefits and drawbacks of using these systems in practice were analyzed.